The challenges of micro enterprises in Malaysia and the prospect for integrated cash waqf micro enterprise investment (ICWME-I) model - Mohd Thas Thaker, Mohamed Asmy; Mohamed, Mustafa Omar (IIUM Press, 2013)
Small and Medium Enterprises (SMEs) have been the backbone of economic growth of many economies. In Malaysia too, SMEs have played a role in contributing to the economy as Malaysia embarks on the journey towards achieving Vision 2020. However, SMEs contribution to Malaysian GDP is still comparatively low. The Malaysian government launched several programs and schemes to boost SMEs activities and development. Hitherto, however, the impact of these programs and schemes are yet to be felt. One reason is that most of the government funding goes to small and medium enterprises, while the largest contributor to SMEs - the micro enterprises have hardly considerable financing assistance. Micro enterprises are considered risky and strict loan conditions have been imposed on them such as collateral, proper support documents and good business track record. Unfortunately, most of them cannot fulfil these conditions. Furthermore, micro enterprises suffer from human resource deficiency. Most of them have less skilled human capital resources with low level of education. Thus, the present study intends to critically survey the literature on the subject. It uses explanatory analysis. Later, it proposes an Integrated Cash Waqf Micro Enterprise Investment (ICWME-I) model as a solution for microenterprises. This model is expected to effectively address their financial and human resource constraints and enhance their contributions to the national income. The study concludes with some suggestions for policy implications